INCREASING AMENDMENT OF TEACHING PROCEDURES IN EDUCATIONAL SYSTEM - Xidirova Nilufar Abdiaxatovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This study looks at different teaching methods in various subjects and shows why they are important for people working in education. Learning good knowledge in a certain subject is an important goal in teaching. In different situations, teachers need to choose the right methods to get good results in learning activities. The results of this study can be used in many schools and educational institutions. It explains the main parts of lesson planning, how teaching works, and what happens in the classroom.